2015
DOI: 10.1016/j.bbamem.2014.12.025
|View full text |Cite
|
Sign up to set email alerts
|

Dendrimers complexed with HIV-1 peptides interact with liposomes and lipid monolayers

Abstract: HIV-peptide/dendrimer complexes interact with model lipid membranes depending on their surface charge. Carbosilane dendrimers can be useful as non-viral carriers for delivering HIV-peptides into cells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 31 publications
0
16
0
Order By: Relevance
“…Distribution of hydrophobic amino acid in MPER can modulate membrane fusion (80,84). Electrostatic interaction between viral particle and negatively charged lipid membrane may also play a role in viral entry (85). Logistic regression analysis indicated an interactive effect of hydropathy and charge of HIV-1 MPER variants on breast milk transmission outcome in our study.…”
Section: Discussionmentioning
confidence: 99%
“…Distribution of hydrophobic amino acid in MPER can modulate membrane fusion (80,84). Electrostatic interaction between viral particle and negatively charged lipid membrane may also play a role in viral entry (85). Logistic regression analysis indicated an interactive effect of hydropathy and charge of HIV-1 MPER variants on breast milk transmission outcome in our study.…”
Section: Discussionmentioning
confidence: 99%
“…Analysis of the fluorescence anisotropy changes of two fluorescent labels, DPH and TMA-DPH, that are located at different membrane depths, confirmed that all tested dendrimers interacted with both regions of membranes and changed membrane fluidity. The observed increase in the fluorescence anisotropy indicated the rising membrane stiffness [29], which in turn reflected the ability of the tested dendrimers to interact with bilayers [30,31]. Phosphorothioate dendrimers of the 5th generation with peripheral hydroxyl groups [32] and viologen-phosphorus dendrimers were also shown to enhance the stiffness of biological membranes, although the intensity of this process was lower [33].…”
Section: Discussionmentioning
confidence: 99%
“…The higher-generation dendrimer has a correspondingly higher zeta potential [5]. Positive charges of both dendrimers indicate that they should readily interact with negatively charged cell membrane [5,23,24]. Due to interaction between dendrimers, they can form aggregates.…”
Section: Discussionmentioning
confidence: 99%